A book for every teacher : teaching English language learners - Li, Nan (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
A Book for Every Teacher: Teaching English Language Learners is a unique and compressive text written for mainstream classroom teachers. The passion for writing this book comes from our working experiences with the K-12 teachers in four school districts through our ELL Center professional development program. Through this program, we provide professional training through our federally funded research and service projects. The purpose of our professional training is to prepare general education teachers to work effectively with English language learners (ELLs). While working with the teachers on a daily basis, we know the immediate needs of the teachers. This motivated us to embark this book project. In recent years, the ELL school population has the highest increase among school populations. As the NEA data indicates, providing ELL students with high quality services and programs is an important investment in America's future (NEA, 2013). This book is our investment in helping teachers to meet their challenges and provide useful information and strategies for teaching ELLs.The book is designed with K-12 teachers in mind. It is best used by teachers who have or will have ELLs in their classrooms and who seek information and strategies to better work with and serve their ELLs to achieve academic success. With this design, teachers can use the book as a text or reference tool. This book can also be adopted as text materials for professional training. Teachers are the most important factor for ELLs' academic success.